Total Versus Single Point Blow-up Solutions for a Semilinear Parabolic Equation (Journal of Partial Differential Equations, 2007)
In this paper, we investigate the blow-up set of solutions of a parabolic equation with localized and non-localized reactions. We completely classify blow-up solutions into total blow-up cases and single point blow-up cases.